Endogenous Entry in Markets with Unobserved Quality - Anthony Creane; Thomas D. Jeitschko (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2012)
In markets for experience or credence goods adverse selection can drive out higher quality products and services. This negative implication of asymmetric information about product quality for trading and welfare, poses the question of how such markets first originate. We consider a market in which sellers make observable investment decisions to enter a market in which each seller's quality becomes private information. Entry has the tendency to lower prices, which may lead to adverse selection. The implied price collapse limits the amount of entry so that high prices are sustained in equilibrium, which results in above normal profits. The analysis suggests that rather than observing the canonical market collapse, markets with asymmetric information about product quality may instead be characterized by above normal profits even in markets with low measures of concentration and less entry than would be expected.
Keywords: D8; D4; L1; 330; adverse selection; asymmetric information; quality; experience goods; cre- dence goods; entry; entry barriers